A Gastrobronchial Fistula Secondary to Endoscopic Internal Drainage of a Post-Sleeve Gastrectomy Fluid Collection - Paraskevas Gkolfakis; Marc-André Bureau; Marianna Arvanitakis; Jacques Devière; Daniel Blero (Korean Society of Gastrointestinal Endoscopy, 2022)
A 44-year-old woman underwent sleeve gastrectomy, which was complicated by a leak. She was treated with two sessions of endoscopic internal drainage using plastic double-pigtail stents. Her clinical evolution was favorable, but four months after the initial stent placement, she became symptomatic, and a gastrobronchial fistula with the proximal end of the stents invading the diaphragm was diagnosed. She was treated with antibiotics, plastic stents were removed, and a partially covered metallic esophageal stent was placed. Eleven weeks later, the esophageal stent was removed with no evidence of fistula. Inappropriate stent size, position, stenting duration, and persistence of low-grade inflammation could explain the patient's symptoms and provide a mechanism for gradual muscle rupture and fistula formation. Although endoscopic internal drainage is usually safe and effective for the management of post-laparoscopic sleeve gastrectomy leaks, close clinical and radiological follow-up is mandatory.